Early theory of mind competencies: Do infants understand others’ beliefs? - Träuble, Birgit; Marinović, Vesna; Pauen, Sabina (Infancy, 2010)
Recent studies suggest that even infants attend to others’ beliefs in order to make sense of their behavior. To warrant the assumption of early belief understanding, corresponding competences need to be demonstrated in a variety of different belief-inducing situations. The present study provides corresponding evidence, using a completely nonverbal object-transfer task based on the general violation-of-expectation paradigm. A total of n = 36 infants (15-month-olds) participated in one of three conditions. Infants saw an actor who either observed an object’s location change, did not observe it, or performed the location change manually without seeing it (i.e., variations in the actor’s information access). Results are in accordance with the assumption that 15-month-old infants master different belief-inducing situations in a highly flexible way, accepting visual as well as manual information access as a proper basis for belief induction.
Gesehen am 22.12.2023